Tendencje rozwojowe współczesnej polszczyzny na podstawie innowacji uzupełniających pochodzących ze współczesnej prozy science fiction - Paczyńska, Ilona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The purpose of this study was to present the potential of fiction as one of the entire source of knowledge about Polish language. The article points out omission of linguistic data coming from literary works in practical culture of language activity, reflected both in source literature and fundamental act – Ustawa o języku polskim. To begin with, authoress short presents criterion for the choice of subject of research, choosing recognized as the most innovatory works (Linia oporu, Perfekcyjna niedoskonałość) of polish SF writer – Jacek Dukaj, as source of potentially the biggest ability of contemporary Polish language development presenting. Based on excerpted supplemental innovations puts across this development (for example: to abbrevation, to precision, internationalisation, linguistic trends, neo-semantization, vulgarization, intertextuality), founded in semantic and word- formative neologisms. Then underlines determinants ensuant artistic language or literary genre and asks the questions about measurability and estimate of these linguistic phenomenon.